Optimization of capacitor bank placement on 70 kV interconnection of Timor System - Tony Koerniawan; Ersalia Dewi Nursita; Maharesmi Apsari (VOLT : Jurnal Ilmiah Pendidikan Teknik Elektro, 2023)
Electric power system voltage quality standards need to be maintained within the limits of applicable quality standards (-10% and +5%). Timor's electricity system in the working area of PT. PLN (Persero) UIW East Nusa Tenggara (NTT) experienced a voltage drop on the 70 kV transmission line, this was caused by the length of the line and the load and the plant was only concentrated on the West side (Kupang). Installing capacitors with the right location and value can increase the power factor as well as increase the system voltage. The Digsilent Powerfactory application-based loadflow analysis method is used to determine the selection of the most optimal location for capacitor placement with the lowest voltage drop indicator. To get the optimum value for the capacitor installation option at one Substation (GI), the lowest voltage drop of 1.66 kV at GI Atambua was obtained. As for the option of laying capacitors in two GIs simultaneously, the lowest voltage drop result of 1.55 kV was obtained by installing capacitors at GI Atambua & Nonohonis.